Sapphic Writing on the Patriarchy – Balkan Lesbian Literature towards Contemporary Social Issues - Cebula, Anna (Mundus Slavicus I, 2025)
This paper is comprised of excerpts from an annual thesis submitted as a part of research for Interfaculty Individual Studies in the Humanities programme. It addresses several social issues depicted in contemporary lesbian literature by Balkan (female) authors, i.e. Biljana Jovanović, Nora Verde, Rene Karabash and Radmila Petrović. The analysis is preceded with a short introduction to lesbian literature characteristics. The patriarchy and heterosexual contract are the main topics covered in the paper. Theoretical basis is formed upon texts by 2nd and 3rd wave feminists: Adrienne Rich, bell hooks, Monique Wittig and Judith Butler.